Analisis Efektivitas Sistem Informasi Akuntansi terhadap Kualitas Pelaporan Keuangan - Iien Rohmatun Nisa (GJET : Global Journal of Educational Technology, 2025)
The rapid development of information technology has encouraged organizations to adopt Accounting Information Systems (AIS) as a primary tool for managing and reporting financial information. The quality of financial reporting is a crucial aspect, as it serves as the basis for managerial decision-making and organizational performance evaluation. This study aims to analyze the effect of Accounting Information System effectiveness on the quality of financial reporting. A quantitative approach with a survey method was employed in this research. Data were collected from 90 respondents who are active users of Accounting Information Systems. The data were gathered through questionnaires using a Likert scale and analyzed using the Statistical Package for the Social Sciences (SPSS). The data analysis procedures included validity testing, reliability testing, normality testing, descriptive statistical analysis, and simple linear regression analysis. The results indicate that the effectiveness of the Accounting Information System has a positive and significant effect on the quality of financial reporting. The coefficient of determination shows that AIS effectiveness contributes substantially to improving financial reporting quality, although other factors outside the research model also play a role. These findings emphasize that optimizing Accounting Information Systems, supported by competent users, can enhance the accuracy, relevance, and timeliness of financial reports.